2009
DOI: 10.3998/ark.5550190.0010.707
|View full text |Cite
|
Sign up to set email alerts
|

Formal synthesis of piperazinomycin, a novel antifungal antibiotic

Abstract: An alternative synthesis of piperazinomycin is disclosed. The approach is based on an intramolecular O-arylation of arylboronic acid with phenol for formation of the macrocyclic biaryl ether.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…As shown in Scheme 7, compound 23 was prepared from 22 via an intramolecular O-arylation of a phenol with an arylboronic acid, and was subsequently transformed into the natural product 24 using a previously reported reduction with borane, followed by O-demethylation. 22 Many other relevant compounds have been obtained by complete reduction of both carbonyl groups in suitable diketopiperazine precursors. Among them, we will mention as illustrative examples the chiral tertiary amines 25, developed as asymmetric catalysts for the Baylis-Hillman reaction, 23 and also polycyclic compounds 26, which were prepared in the course of a pharmacophore search for allosteric ligands of the muscarinic M 2 receptor 24 (Scheme 8).…”
Section: Synthetic Methods Involving the Reduction Of Dkp Carbonyl Gr...mentioning
confidence: 99%
“…As shown in Scheme 7, compound 23 was prepared from 22 via an intramolecular O-arylation of a phenol with an arylboronic acid, and was subsequently transformed into the natural product 24 using a previously reported reduction with borane, followed by O-demethylation. 22 Many other relevant compounds have been obtained by complete reduction of both carbonyl groups in suitable diketopiperazine precursors. Among them, we will mention as illustrative examples the chiral tertiary amines 25, developed as asymmetric catalysts for the Baylis-Hillman reaction, 23 and also polycyclic compounds 26, which were prepared in the course of a pharmacophore search for allosteric ligands of the muscarinic M 2 receptor 24 (Scheme 8).…”
Section: Synthetic Methods Involving the Reduction Of Dkp Carbonyl Gr...mentioning
confidence: 99%
“…228 Scheme 9 Copper-mediated macrocyclization reactions used in the preparation of 73. 160,238 Another copper-induced macrocyclization applied for the formation of the aryl-aryl ether bond was described by Sen in 2009 (Scheme 9, right). 238 Here, the Chan-Lam-Evans procedure was used, [239][240][241] producing the cyclic intermediate 87 from the boronic acid 86.…”
Section: Isodityrosine-containing Peptidesmentioning
confidence: 99%
“…160,238 Another copper-induced macrocyclization applied for the formation of the aryl-aryl ether bond was described by Sen in 2009 (Scheme 9, right). 238 Here, the Chan-Lam-Evans procedure was used, [239][240][241] producing the cyclic intermediate 87 from the boronic acid 86. This reaction proceeded at room temperature, but gave the constrained diketopiperazine 87 only in 33% yield.…”
Section: Isodityrosine-containing Peptidesmentioning
confidence: 99%
“…An efficient approach to the green synthesis of glycoluryls in an aqueous medium using P 4 O 10 as a catalyst, under mild conditions with the possibility of recycling both solvent and catalyst, is reported in Ref. [39] More recently, in a number of works [40][41][42] it was found that etidronic acid (HEDP) proved to be a convenient "green" catalyst in 3-component reactions of the formation of dihydropyrimidones using carbonyl compounds with an active methylene group, urea and aldehydes as under traditional conditions, [40,41] and under microwave synthesis. [42] However, examples of the use of HEDP as a catalyst in the reactions of 1, 2-dicarbonyl compounds with ureas are still not known.…”
Section: Introductionmentioning
confidence: 99%